The Bacterial Oral Microbiome in Children with Congenital Heart Disease: An Extensive Review - Hofmann, Maria; Schulz-Weidner, Nelly; Krämer, Norbert; Hain, Torsten; Justus Liebig University Giessen (My University, 2023)
Children with congenital heart disease have poorer oral health compared with healthy children. Oral diseases, such as dental caries and gingivitis, are associated with the oral microbiome. The objective of this review was to find evidence of differences in the bacterial colonization of the oral cavity of children with congenital heart disease (CHD) versus healthy children. A literature review was conducted according to predetermined criteria, including the need for controlled clinical trials. Half of the 14 studies that met the inclusion criteria reported significant differences in bacterial colonization in children with congenital heart disease. A variety of influencing factors were discussed. There is some evidence for alterations in the oral microflora as a result of physiopathological and treatment-related factors in children with CHD, but additional research is required to validate these findings.
Keywords: ddc:610